On the borders of Linguistics as a science and as an academic discipline - GRDZELYAN, ROUZAN (Bulletin of Yerevan University H: Russian Philology, 2021)
Article is devoted to clarifying the subject of modern Linguistics from the perspective of the anthropocentric scientific paradigm. An attempt is made to clarify the importance of Linguistics, on the one hand, in the context of philology, and on the other hand, in the context of the overall humanitarian knowledge. In our days anthropocentric Linguistics stimulated development of interdisciplinary relationships and the emergence of new linguistic subjects.
Keywords: the object of linguistics, philology, humanitarian knowledges, interdisciplinary links, linguistic subjects